Implementation of Gender Responsive Learning in Bhayangkari Kindergarten of Ruteng - Adriani Tamo Ina Talu; Elisabeth Sarinastitin (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2020)
This research is motivated by the existence of learning practices that lead to gender responsive learning in Bhayangkari Ruteng Kindergarten. The research objectives are (1) to know the description of gender responsive learning practiced by schools, (2) Comparing whether what is practiced by schools is in accordance with gender responsive learning indicators or not. (3) knowing the gender responsive learning model developed by Bhayangkari Kindergarten. The research method used is qualitative descriptive research. The research subjects consisted of principals, teachers and kindergarten children. Data collection is done using interview instruments, observation sheets and documentation studies. The research data were analyzed using the Miles and Huberman analysis model which included the reduction, display and verification processes. The results of the study show first, the learning process carried out at Bhayangkari Kindergarten has met the norms of gender equality and justice seen from the learning planning process, teaching and learning interactions, classroom management and learning evaluation. However, the choice of playing tools and materials carried out by children during learning is still influenced by the community stereotypes about playing the tools and materials played by women and men. Second, Bhayangkari Kindergarten has developed a learning process based on indicators of gender responsive learning in early childhood by giving equal opportunities to women and men to gain access and active participation in learning, obtaining the same rights and obligations in the learning process, obtaining services that the same and obtain the same teaching materials. Third, to develop gender responsive learning in Bhayangkari Kindergarten, the school pays attention to grouping children while playing and learning. The group formed takes into account the diversity of children in terms of ability, culture and religion. In addition, in learning, the teacher gives children the opportunity to learn based on children's interests so that children are given the freedom to choose games according to their interests.Keywords: Gender Responsive Learning, Kindergarten